2019
DOI: 10.1007/s00520-019-05166-5
|View full text |Cite
|
Sign up to set email alerts
|

Utility of topical agents for radiation dermatitis and pain: a randomized clinical trial

Abstract: Purpose-Although topical agents are often provided during radiation therapy, there is limited consensus and evidence for their use prophylactically to prevent or reduce radiation dermatitis. Methods-This was a multi-site, randomized, placebo-controlled, blinded study of 191 breast cancer patients to compare the prophylactic effectiveness of three topical agents (Curcumin, HPR Plus™, and Placebo) for reducing radiation dermatitis and associated pain. Patients applied the topical agent to their skin in the radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 40 publications
(37 reference statements)
0
26
1
1
Order By: Relevance
“… 4 Various topical treatments have been examined in clinical trials, such as aloe Vera gel, hyaluronate creams, Calendula, petrolatum, sucralfate cream, Curcumin gel, Chamomile gel, and dressings; but the results were conflicting in reducing skin symptoms. 7 , 8 , 9 Also, recent publications recommend the use of topical corticosteroids. 7 , 10 Overall, in most institutions, physicians prescribe topical agents, such as Aquaphor, aloe Vera, or silver sulfadiazine after the onset of evident skin alterations.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Various topical treatments have been examined in clinical trials, such as aloe Vera gel, hyaluronate creams, Calendula, petrolatum, sucralfate cream, Curcumin gel, Chamomile gel, and dressings; but the results were conflicting in reducing skin symptoms. 7 , 8 , 9 Also, recent publications recommend the use of topical corticosteroids. 7 , 10 Overall, in most institutions, physicians prescribe topical agents, such as Aquaphor, aloe Vera, or silver sulfadiazine after the onset of evident skin alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these approaches have been described in detail above and in other chapters of this special issue (e.g., mesenchymal stromal cells derived from a variety of sources), so this section will focus on novel therapies that are at various stages of product development. These approaches range from nutraceuticals such as oral or topical curcumin [ 114 , 141 , 142 ] and drugs targeting the vasculature [ 143 ] to advanced wound care (Silverlon® dressings) and structural (KeraStat® cream) products. Detailed information about many of the approaches discussed here has been previously published [ 133 ].…”
Section: Current Researchmentioning
confidence: 99%
“…In a randomized, placebo-controlled, blinded study of 191 breast cancer patients, curcumin was applied topically on the irradiated skin daily for a week after irradiation completion. In patients with high breast separation (≥25 cm), who may have the worst skin reactions, curcumin was found to be effective in minimizing RT dermatitis and pain [ 64 ]. In another randomized, double-blinded, placebo-controlled trial of 686 breast cancer patients, however, in which patients received 500-mg capsules of curcumin three times daily for up to 1-week after radiation therapy, no significant reduction in RT dermatitis severity was observed compared to the placebo group [ 65 ] ( Table 2 ).…”
Section: Radioprotection By Curcuminmentioning
confidence: 99%
“…Topical application of curcumin showed a significant therapeutic effect in patients with oral submucous fibrosis particularly in combination with triamcinolone and hyaluronidase [ 88 ]. In a multi-site, randomized, placebo-controlled, blinded study of 191 breast cancer patients, topical application of curcumin was found to help reduce radiotherapy-associated dermatitis and pain [ 64 ]. There is also, accumulating evidence to suggest the potential anti-neoplastic activity of curcumin against HNCs [ 89 , 90 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%